Financial Literature And Interest Of Aceh People In Transactions In Sharia Financial Institutions Post Implementation Of Qanun Sharia Financial Institutions In Aceh - Mai Simahatie; Marliyah Marliyah; Zulkifli Yusuf (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
Financial literacy is a very important element of knowledge for the economic progress of a country because it is closely related to public interest, the higher the level of public financial literacy, the easier it is for the financial system to be accepted in the community to be implemented and contribute to the economic growth of a region, because with The high level of financial literacy in the community, the easier it will be for financial institutions to provide financial access to the public. the enactment of qanun no 11 of 2018 regarding Islamic financial institutions in Aceh has begun since January 4, 2019, all financial institutions in Aceh. In this study, the data used is secondary data obtained from scientific references as quoted from journals, books texts, working papers, national and international scientific forums and other sources deemed relevant to this research. the results of the research and discussion, it can be concluded that nationally the financial literacy of the Indonesian people is still relatively low, but for the Aceh region itself it is higher than the level of public understanding of sharia finance in Aceh which is above the average public understanding of sharia banking nationally. The interest of the Acehnese people in transacting in Islamic banking is currently increasing, as can be seen from the increasing graph in terms of assets, financing, and third party funds, especially in 2021.